The Incidences and Related CT Features of Vascular Lake Phenomenon on Angiography Before Chemoembolization - Yang, Kai-Lun; Guo, Ya-Pan; Mao, Xin-Yu; Shen, Jian; Zou, Jian-Wei; Li, Ming-Ming; Li, Zhi (Cardiovascular and interventional radiology, 2024)
Purpose To elucidate incidence rates of vascular lake phenomenon (VLP) in hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (ICC), hepatic metastasis (HMT) on transarterial angiography before chemoembolization, and to identity CT features predictive for it. Materials and Methods A comprehensive evaluation involved 665 subjects for incidence analysis, comprising 527 of HCC, 33 of ICC and 105 of HMT. VLP was characterized as intratumoral contrast material pool persisting late into venous phase. Incidences were cataloged on both super-selective and common hepatic artery angiography. For CT features analysis, a subset of 182 cases were analyzed. Enhancement ratio served as an index for comparative analysis of nodule enhancement degrees. Results In HCC, incidence of VLP ascertained via super-selective angiography was 13.5%, whereas it as 7.8% on common hepatic artery angiography. Remarkably, no incidences of VLP were recorded in either ICC or HMT cases. On pre-interventional CT, the prevalence of pseudocapsule was statistically greater in VLP group than Non-VLP group (66.6% vs. 37.6%, P = 0.015). The Houndsfield units (HU) of tumors in plain scan ( P = 0.007), arterial phase ( P = 0.001), venous phase ( P = 0.041), arterial phase enhancement ratio ( P < 0.001) were statistically higher in VLP group compared to Non-VLP group. Arterial phase enhancement ratio ( P = 0.025), presence of pseudocapsule ( P = 0.001), HU of tumor in plain scan ( P = 0.035) serve as independent risk factors for VLP manifestation. Conclusion VLP is a distinct angiography phenomenon uniquely associated with HCC. High arterial phase enhancement ratio, presence of pseudocapsule, high HU of tumor in plain scan are independent risk factors for VLP.